PENATALAKSANAAN TREMOR TERKINI - Tumewah, Rizal (Jurnal Biomedik : JBM, 2015)
Abstract: Not all tremors are Parkinson’s neither pathologic. Some of the tremor therapies have small advantage and some not at all. Therefore, with the better understanding of the causes of tremor, therapists can determine the most effective and minimal adverse effects of therapies. Tremor is the most frequently symptom that can be detected on the movement disorder group. Characteristics of tremor are: rhythmic, oscillatory movement of hands, head, neck or trunk; voice trembling; difficulties in writing and drawing; and problems in holding or controlling things. Tremor can be evoked in a normal state, pathologic conditions, such as psychogenic, metabolic, drug-induce and toxicity conditions, as well as in idiopathic conditions; thus, the therapies have to be various depended on the causes. Occasionally, symptomatic medical therapies can be given to the specific type of tremor. Surgical treatments like thalamotomy, pallidotomy, and thalamic stimulation may be used to treat severe or disabling tremor which is failed with medical treatment. Current treatment of tremor based on Consensus of Movement Disorder Society emphasized the need to classified tremors based on the etiopathogenesis, clinical features, and additional examination in order to achieve more favorable outcome in tremor treatment.Keywords: tremor, current treatment, etiopathogenesis, clinical features, additional examination, medical and surgical treatmentAbstrak: Tidak semua tremor itu Penyakit Parkinson dan tidak semua tremor itu patologik. Umumnya terapi tremor tidak terlalu bermanfaat dan kadang tidak ada perbaikan. Dengan adanya pemahaman mengenai penyebab tremor, para klinikus dapat memberikan terapi yang efektif dengan efek samping minimal. Tremor merupakan salah satu gejala yang paling sering ditemukan dari kelompok movement disorders. Karakteristik tremor dapat berupa getaran yang berirama pada tangan, lengan, kepala, leher, atau tubuh; suara bergetar; kesulitan menulis dan menggambar; serta bermasalah dalam memegang dan mengontrol benda. Tremor dapat ditemukan pada keadaan normal, keadaan patologik akibat psikogenik, penyakit pada sistem saraf, metabolik, obat-obatan, keracunan, bahkan idiopatik sehingga terapinya pun bervariasi tergantung dari penyebab. Kadang terapi medikamentosa simptomatik dapat diberikan pada tipe tremor tertentu. Pembedahan seperti thalamotomy, pallidotomy, dan thalamic stimulation biasanya dilakukan pada kasus tremor yang berat atau gagal dalam pengontrolan dengan terapi medikamentosa. Terapi tremor terkini berdasarkan konsensus Movement Disorder Society menekankan perlunya pendekatan klasifikasi tremor berdasarkan etiopatogesis, gejala klinis, dan pemeriksaan penunjang untuk menentukan keberhasilan dalam menangani pasien tremor.Kata kunci: tremor, terapi terkini, etiopatogenesis, gejala klinis dan pemeriksaan penunjang, medikamentosa, pembedahan